Precise Analgesic Instructions Improve Narcotic Usage: A Randomized Trial. (4th January 2022) - Erz, Logan; Larson, Brandon; Mirhaidari, Shayda; Cook, Chad; Wagner, Doug
Abstract: Background: Given the ongoing battle with opioid abuse and overuse in the United States, new strategies are consistently being implemented to reduce opioid utilization and overprescribing. Objectives: The purpose of this study was to determine if a more regulated explicit pain management instruction plan could reduce the number of opioids taken. Methods: Blinded randomized prospective study comparing a total of 110 (Group A = 55, Group B = 55) women who underwent elective outpatient bilateral breast reduction surgery by 2 different plastic surgeons. Patients were randomly divided into either Group A (control) that received general pain management instructions or Group B (experimental) that received explicit pain management instructions from the surgeons and nurses. Participants were asked to record the number of times they treated their pain with each separate modality. They were also asked to record their average daily pain scale for the days that they were treating their pain. Results: Patients in Group B took on average 1.5 oxycodone (5 mg) and patients in Group A took on average 5.7 oxycodone (5 mg) ( P  < 0.01). Thirty-four patients in Group B took no oxycodone. Patients in Group B also had statistically significant lower subjective pain scores. Conclusions: Based on these results, it appears that standardizing how patients are instructed to treat their pain postoperatively may reduce the number of narcotics needed, thus reducing the number of narcotics prescribed without compromising pain control. Level of Evidence: 2: